Identification of Mammalian Proteins That Collaborate with Type III Secretion System Function: Involvement of a Chemokine Receptor in Supporting Translocon Activity - Kerri-Lynn Sheahan (American Society for Microbiology, 2015)
ABSTRACT The type III secretion system (T3SS) is a highly conserved protein delivery system found in multiple Gram-negative pathogens, including Yersinia pseudotuberculosis. Most studies of Yersinia species type III intoxication of host cells have focused on the bacterial determinants that promote assembly and function of the secretion system. In this study, we performed a pooled RNA interference (RNAi) screen to identify mammalian host proteins required for the cytotoxic effects associated with the Yersinia translocated substrate YopE, a GTPase-activating protein (GAP) that inactivates the small Rho GTPases. Cell populations were positively selected for short hairpin RNAs (shRNAs) that interfere with YopE activity using a combination of fluorescence resonance energy transfer (FRET) and flow cytometry, and the degree of enrichment was determined by deep sequencing. Analysis of the candidates identified by the enrichment process revealed that many were important for the initial step of Y. pseudotuberculosis T3SS function, YopB/D pore formation. These candidates included shRNA that depleted downstream effectors of RhoA signaling, coated pit formation, and receptors involved in cell signaling, including the chemokine receptor CCR5 (chemokine [C-C motif] receptor 5). Depletion of CCR5 in 293T cells yielded a defect in YopB/D pore formation and effector translocation, while both phenotypes could be complemented by overexpression of CCR5 protein. Yop effector translocation was also decreased in isolated primary phagocytic cells from a Ccr5−/− knockout mouse. We postulate that CCR5 acts to promote translocation by modulating cytoskeletal activities necessary for proper assembly of the YopB/D translocation pore. Overall, this study presents a new approach to investigating the contribution of the host cell to T3SS in Y. pseudotuberculosis. IMPORTANCE Many Gram-negative bacteria require type III secretion systems (T3SS) for host survival, making these highly specialized secretion systems good targets for antimicrobial agents. After the bacterium binds to host cells, T3SS deposit proteins into the cytosol of host cells through a needle-like appendage and a protein translocon channel. Translocation of proteins via this system is highly regulated, and the contribution of the host cell in promoting assembly and insertion of the channel into the plasma membrane, folding of the bacterial proteins, and trafficking of these substrates are all poorly characterized events. In this study, we identified host cell proteins important for activity of YopE, a Yersinia pseudotuberculosis T3SS-delivered protein. The results demonstrate that insertion and assembly of the translocon are complex processes, requiring a variety of membrane trafficking and cytoskeletal processes, as well as a surprising role for cell surface signaling molecules in supporting proper function.